2021
DOI: 10.7717/peerj.12137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a natural precipitation gradient on fish and macroinvertebrate assemblages in coastal streams

Abstract: Anthropogenic climate change is expected to increase the aridity of many regions of the world. Surface water ecosystems are particularly vulnerable to changes in the water-cycle and may suffer adverse impacts in affected regions. To enhance our understanding of how freshwater communities will respond to predicted shifts in water-cycle dynamics, we employed a space for time approach along a natural precipitation gradient on the Texas Coastal Prairie. In the spring of 2017, we conducted surveys of 10 USGS-gauged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…It is possible that the hurricane impacts created a state shift in the streams resulting in a permanent deviation from pre‐hurricane community structure and function. However, a survey of streams along the same rainfall gradient in the region performed in April of 2017 show a similar pattern of community composition changing along the rainfall gradient to what we observed in this study (Kinard et al., 2021), indicating that the regional patterns of interest had not changed. Furthermore, the presence of a state shift caused by the hurricane would run counter to our general understanding of streams as being highly resilient in the face of short‐term perturbations (Lytle & Poff, 2004; Poff, 1996; Resh et al., 1988).…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that the hurricane impacts created a state shift in the streams resulting in a permanent deviation from pre‐hurricane community structure and function. However, a survey of streams along the same rainfall gradient in the region performed in April of 2017 show a similar pattern of community composition changing along the rainfall gradient to what we observed in this study (Kinard et al., 2021), indicating that the regional patterns of interest had not changed. Furthermore, the presence of a state shift caused by the hurricane would run counter to our general understanding of streams as being highly resilient in the face of short‐term perturbations (Lytle & Poff, 2004; Poff, 1996; Resh et al., 1988).…”
Section: Discussionsupporting
confidence: 88%
“…All sites were wadable and had a U.S. Geological Survey (USGS) flow gauge within 200 m of the sampling area. Previous work on this study system revealed that rainfall driven variation in hydrology and environmental conditions is the dominant driver of stream invertebrate community structure (Carvallo et al, 2022;Kinard et al, 2021).…”
Section: Study Areamentioning
confidence: 83%
“…We hypothesized that semi‐arid stream invertebrate communities would exhibit quick return times to a baseline following the storm event because these communities regularly experience more extreme flow conditions and, as a result, have higher richness and abundance of fast colonizers and strong dispersers (see Carvallo et al., 2022; Kinard et al., 2021). In contrast, communities in sub‐humid streams were expected to have slower recovery times because these streams typically experience longer flood durations with more gentle rising and falling limbs (Dodds et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The first is community composition, which includes species composition [e.g. identity, richness (Nooten, Andrew & Hughes, 2014; Niu et al ., 2019; Kinard, Patrick & Carvallo, 2021)] and trait (or functional type) composition (Dubuis et al ., 2013; de Oliveira et al ., 2020). This includes metrics such as the community temperature/precipitation index (CTI/CPI), which captures the climate conditions encountered within the geographic ranges of the species within a community (Devictor et al ., 2012).…”
Section: Application Of Sfts To Climate–biotic Relationshipsmentioning
confidence: 99%